PERAN PASANGAN DALAM KEBERLANGSU PERAN PASANGAN DALAM KEBERLANGSUNGAN MENYUSUI : TINJAUAN SISTEMATIK STUDI KUALITATIF: PERAN PASANGAN DALAM KEBERLANGSUNGAN MENYUSUI : TINJAUAN SISTEMATIK STUDI KUALITATIF - Pratiwi, Bintang Agustina; Kartini, Apoina; Jati, Sutopo Patria; Sriatmi, Ayun (Amerta Nutrition, 2023)
Background: Breast milk is optimal for infant nutrition, and to ensure its sustained practice, maternal assistance from partners is essential, so that the breastfeeding process runs according to the expectations of the couple. Objectives: To identify the forms of support offered by partners for breastfeeding continuity. Methods: This research was conducted through a systematic review of qualitative research using three databases, namely PubMed, Scopus, and ScienceDirect, published from 2014 to 2023. The JBI Critical Appraisal Checklist for Qualitative Research was utilized to critically evaluate the included publications, resulting in the inclusion of five studies. Results: Within the breastfeeding context, "husband support" can refer to several types of assistance, including emotional support, seeking breastfeeding information, helping with the mother's work, assisting in parenting responsibilities, and confiding in the mother and financial support. Only two of the seven studies indicated receiving financial support to replace the husband's role. Support from a partner makes a mother feel more confident about breastfeeding her baby. A positive response from the partner will help the mother feel more comfortable while breastfeeding her child. Conclusions: This systematic review provides a valuable reference for future research development by considering the phenomenon of spousal support for breastfeeding participation.